2016
DOI: 10.1136/bjophthalmol-2015-308291
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathology and histopathology of conjunctival biopsies in patients with presumed idiopathic punctal stenosis

Abstract: Background/Aims Numerous processes have been implicated as causes of punctal stenosis. Recent studies have highlighted inflammation in punctoplasty specimens in patients with punctal stenosis. Conjunctival biopsy has been suggested as a means to determine underlying etiologies, although little is known regarding what conjunctival pathologies are associated with punctal stenosis. Our objective is to examine the pathologic and immunologic findings in conjunctival biopsy specimens in patients with presumed idiopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In those studies; specimens from the puncti were examined showing evidence of chronic inflammation in the majority of specimens (83 and 100 % of the cases). In a later published study, 97.2% of the conjunctival specimens displayed inflammatory infiltrates, which further validates the prior results regarding the proposed inflammatory mechanism of acquired punctal stenosis [20]. Outstandingly, all patients in their study were diagnosed with presumed idiopathic punctal stenosis.…”
Section: Discussionsupporting
confidence: 82%
“…In those studies; specimens from the puncti were examined showing evidence of chronic inflammation in the majority of specimens (83 and 100 % of the cases). In a later published study, 97.2% of the conjunctival specimens displayed inflammatory infiltrates, which further validates the prior results regarding the proposed inflammatory mechanism of acquired punctal stenosis [20]. Outstandingly, all patients in their study were diagnosed with presumed idiopathic punctal stenosis.…”
Section: Discussionsupporting
confidence: 82%
“…Research on idiopathic lacrimal punctal blockage is scant at best. All stenotic puncta were found to have subepithelial and subconjunctival fibrosis, according to histological and electro-microscopic examinations, but there was also significant inflammation and high immunoreactivity [9]. The current study aimed to explore medical therapy for treating idiopathic, non-infectious acquired puncta inflammation, which has not been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…The punctum is the entry point for tears, and it is vulnerable to exogenous or endogenous irritants that could initiate the inflammatory process [ 5 , 16 ]. Inflammation, which is the physiological defence mechanism against various noxious stimuli, and subsequent fibrosis appear to be the currently proposed mechanism in the development of punctal stenosis [ 5 , 16 – 19 ]. Various histopathological studies have reported that inflammation and/or fibrosis were the main histopathological features, with rates ranging from 73 to 100% in punctal stenosis specimens [ 15 , 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, which is the physiological defence mechanism against various noxious stimuli, and subsequent fibrosis appear to be the currently proposed mechanism in the development of punctal stenosis [ 5 , 16 – 19 ]. Various histopathological studies have reported that inflammation and/or fibrosis were the main histopathological features, with rates ranging from 73 to 100% in punctal stenosis specimens [ 15 , 17 19 ]. There is plentiful evidence that cellular stress conditions caused by oxidative stress and low-grade inflammation constitute the main mechanism involved in the pathogenesis of the fibrotic process in PXF [ 10 , 11 , 20 22 ].…”
Section: Discussionmentioning
confidence: 99%